Features of state target programs and projects monitoring - Efanova O. A. (Interactive science, 2018)
specifics of actions on state target programs and projects monitoring as managerial tool are considered in article. Its difference from assessment of their quality comes to light, the role and the need of relation measurement of target audience to the held events is emphasized.
Keywords: мониторинг; эффективность; оценка; показатели; целевая программа; efficiency; monitoring; indicators; assessment; target program